Doxycycline post-exposure prophylaxis in China: current utilized situation among men who have sex with men in a cross-sectional online survey from two cites - Xu Zhang; Fang-Zhi Du; Xiao-Li Zheng; Rui-Li Zhang; Qian-Qiu Wang (BMC Public Health)
Abstract Background Doxycycline post-exposure prophylaxis (Doxy-PEP) represents an emerging strategy for STI prevention. Self-administered use of Doxy-PEP has been empirically observed among men who have sex with men (MSM) in some countries, while little is known about current use of it in the Chinese population. Methods An online survey was conducted among MSM in two cities in China. We detected the current utilized situation of Doxy-PEP with descriptive statistics and constructed χ2 or Fisher’s exact tests for factors associated with self-administered Doxy-PEP use. Results Three hundred thirteen individuals returned the results of the questionnaire. Most of them under 35 years of age (79.55%), had college degrees (70.61%) and worked in private institutions (36.42%) or were freelancers (24.28%). 34.2% had heard of Doxy-PEP and 12.1% had used it, while 8.31% were self-initiated users. Doxy-PEP self-initiated use behavior was found to be associated with multiple sexual partners (P = 0.013) and HIV PrEP/PEP experience (P < 0.001). 89.47% of the Doxy-PEP users showed interest in promoting it to others in the future. Conclusion Self-initiated use of Doxy-PEP is prevalent among Chinese MSM, and should be taken into consideration for future public health intervention programs aimed at promoting and implementing Doxy-PEP in China.